Weaknesses and Opportunities in Implementing Public Service Policy in the Government of Palembang, Indonesia - Hardiyansyah - (Journal of Social and Development Sciences, 2017)
The enactment of Indonesian law No. 25 of 2009 on Public Service is a milestone and a hope to the realization of public services quality. The substance of this law has led to the implementation of public services quality expected by all parties (stakeholders). This article is about to discuss the implementation of public service policy in Palembang. By using qualitative descriptive method, the conclusion showed that there are some weaknesses in the implementation of public service policy: (1) the information submitted is inaccurate, incomplete, inchoate; (2) Staffing / apparatus are still not in accordance with the disciplines and expertises; (3) Unclear job descriptions and procedures, by who does the job and to whom should be the report submitted; (4) The use of facilities, infrastructure is not optimal use; (5) The behavior of officers and management commitments are still low; (6) The incentives expected are still in material / value for money; (7) Awards and supports given to the implementor are still very low; (8) The organizational structure is "gemuk/tambun" (increasing); (9) Duplication of duties and functions among related agencies. While the opportunities that can be exploited are: (A) The use of information technology using online services; (B) Higher educational qualifications of apparatus; (C) Some facilities and infrastructures have been adequate; (D) With the slogan "Miskin struktur dan Kaya fungsi" (lean and mean) is expected to realize the organizational structure more effective, efficient, and easier for public services.